On the Scientific Validity of the Program of Work of a Psychologist with Teaching Staff and Teachers on the Prevention of Suicidal Risks in the Educational Organization “I Choose Life!” - Seryakina, A.V.; Ramzaeva, V.Yu (Bulletin of Practical Psychology of Education, 2023)
The authors of the article pose the question: are modern teachers ready to participate in solving the problem of adolescent suicide, and come to the conclusion that, despite the large number of different diagnostic tools and literature, they are not ready to use them in practice. To solve this and other issues, the authors propose to carry out a system of measures related to increasing the competence of the teaching staff, developing their practical skills, motivational and psychological readiness to carry out work on the prevention of suicidal risks. This system formed the basis of the program of work of the educational psychologist with teaching staff and teachers "I choose life!" The implementation of the program contributes to the formation of a safe educational environment, the prevention of destructive behavior, suicidal and other risks. It was tested on the basis of the state autonomous institution of additional professional education "Saratov Regional Institute for Educational Development" as part of the implementation of an additional professional development program "Strategies for the work of an educational organization with the problem of suicidal behavior of minors" for class teachers, educational psychologists and heads of educational organizations. The program "I choose life!" passed an examination to verify the evidence base within the section "Evidence-Based Approach in Psychology and Education" of the Scientific Expert Council of the Federal State Budgetary Educational Institution of Higher Education MSUPE with the assignment of a certificate of conformity (registration number "7/17-pr" dated July 25, 2023). Based on the results of the examination, it was found to comply with the standards of programs and technologies with proven effectiveness for the educational and social spheres, taking into account additional recommendations, and was recommended for inclusion in the register of exemplary correctional and developmental, correctional, rehabilitation and preventive programs for the activities of a teacher-psychologist (psychologist in the field of education ) and replication in educational and social institutions. Авторы статьи ставят вопрос: готовы ли современные педагоги к участию в решении проблемы подросткового суицида, и приходят к выводу, что, несмотря на большое количество различного диагностического инструментария, литературы, они не готовы к их применению на практике. Для решения этого и других вопросов авторы предлагают проводить систему мероприятий, связанных с повышением компетентности педагогического коллектива, формированием у них практических навыков, мотивационной и психологической готовности к проведению работы по профилактике суицидальных рисков. Данная система легла в основу программы работы педагога-психолога с педагогическими коллективами и педагогами «Я выбираю жизнь!». Реализация программы способствует формированию безопасной образовательной среды, профилактике деструктивного поведения, суицидальных и других рисков. Она прошла апробацию на базе государственного автономного учреждения дополнительного профессионального образования «Саратовский областной институт развития образования» в рамках реализации дополнительной профессиональной программы повышения квалификации «Стратегии работы образовательной организации с проблемой суицидального поведения несовершеннолетних» для классных руководителей, педагогов-психологов и руководителей образовательных организаций. Программа «Я выбираю жизнь!» прошла экспертизу по верификации доказательной базы в рамках секции «Доказательный подход в психологии и образовании» Научно-экспертного совета ФГБОУ ВО МГППУ с присвоением сертификата соответствия (регистрационный номер «7/17-пр» от 25.07.2023). По результатам экспертизы была признана соответствующей стандартам программ и технологий с доказанной эффективностью для сферы образования и социальной сферы с учетом дополнительных рекомендаций и рекомендована для включения в реестр примерных коррекционно-развивающих, коррекционно-реабилитационных и профилактических программ для деятельности педагога-психолога (психолога в сфере образования) и тиражирования в учреждениях образования и социальной сферы.